(untitled) (MMIT Proceedings, 2025)
The article explores the use of didactic games in the process of training philology students with the aim of improving their speech competence. The effectiveness of game-based methods in developing communicative skills, increasing motivation for language learning, and enhancing speech activity is substantiated. Examples of specific games used in classroom practice are provided